2020
DOI: 10.18235/0003123
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Hiring Instruments and Teacher Value Added: Evidence from Peru

Abstract: In this article, we explore whether the evaluation instruments used to recruit teachers in the national teacher hiring process in Peru are good predictors of teacher effectiveness. To this end, we estimate teacher value-added (TVA) measures for public primary school teachers in 2018 and test for their correlation with the results of the 2015 and 2017 national evaluations. Our findings indicate that among the three sub-tests that comprise the first, centralized stage of the process, the curricular and pedagogic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…For example, Cruz-Aguayo et al (2017) found no evidence that teacher evaluation processes used in Ecuador-including a written test, a demonstration class, and other measurements-could predict teacher effectiveness in improving student learning outcomes. Meanwhile, Bertoni et al (2020) evaluated the teacher hiring system in Peru, which consists of two stages: a centralized and decentralized selection processes. The authors reported mixed results in terms of the correlation between teacher screening tests and teacher performance measurement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cruz-Aguayo et al (2017) found no evidence that teacher evaluation processes used in Ecuador-including a written test, a demonstration class, and other measurements-could predict teacher effectiveness in improving student learning outcomes. Meanwhile, Bertoni et al (2020) evaluated the teacher hiring system in Peru, which consists of two stages: a centralized and decentralized selection processes. The authors reported mixed results in terms of the correlation between teacher screening tests and teacher performance measurement.…”
Section: Introductionmentioning
confidence: 99%
“…• More generally, using multiple, tailored assessments can improve the accuracy screening processes. An analysis of Peru's centralised assessment for pre-service teacher education graduates, comprising assessments on reading comprehension, logical reasoning, and curricular and pedagogical knowledge, found (perhaps unsurprisingly) that the combined assessment score was more strongly correlated with teachers' subsequent value-added scores in the classroom than were any of the three assessment components individually (Bertoni et al, 2020). (See also Malinen et al, 2012, on Finland's multistage screening process for entry into pre-service teacher education, as mentioned in Section 4.2 below.…”
mentioning
confidence: 99%